Dysphagia diagnosis and treatment - Ekberg, Olle (Medical Radiology, 2012)
This book provides a comprehensive and up-to-date description of the diagnosis and management of dysphagia, with particular reference to oral and pharyngeal dysfunction. All aspects of dysphagia are covered, from anatomy and physiology to patient care. Alongside descriptions of a variety of disease entities, signs and symptoms, and treatment approaches, many other relevant topics are addressed, including endoscopic and manometric aspects, malnutrition and dehydration, the psychiatric burden, and features specific to pediatric and geriatric patients. The authors are without exception renowned experts in their field. This book will be of value to all specialists involved in the evaluation and treatment of dysphagia, including ENT surgeons, thoracic surgeons, speech and language pathologists, phoniatricians, gastroenterologists, neurologists, and radiologists.